Anxiety, Depression, Coping Styles, and Perceived Social Support Among University Students: A Mediation and Moderation Analyses - Parungao, Arold (Journal of Interdisciplinary Perspectives, 2024)
This study examined the association between anxiety, depression, social support, and coping strategies, particularly among higher education students undergoing a distinct developmental transition phase and confronting substantial difficulties. A quantitative approach utilizing inquiry techniques such as surveys and experiments was used with a sample of six hundred eighty-five (685) higher education students enrolled at a State University. Based on the results, the researcher concluded that higher education students exhibited moderate levels of anxiety and depression. The study identified that these students engage moderately in problem-focused, emotion-focused, and avoidance-focused coping, showing diverse strategies to address stress. They also reported moderate perceived social support, emphasizing the importance of relationships with family, friends, and significant others. A significant positive relationship was found between elevated anxiety levels and increased depressive symptoms. Coping styles were significant in mediating the impact of anxiety on depression, with problem-focused coping being a major mediator. Emotion-focused and avoidance-focused coping also significantly mediated this relationship. Contrary to expectations, perceived social support did not significantly moderate the relationship between anxiety and depression. Family support showed a trend toward moderating the anxiety-depression relationship, suggesting a potential influence that needs further exploration. Support from friends and significant others, such as romantic partners and mentors, did not significantly affect this relationship, indicating that these types of support may not be crucial in this context.